Impact of Information Asymmetry on Return Volatility – Domestic and Cross-Country Evidence - N., Shabarisha; Madegowda, J. (Indian Journal of Research in Capital Markets, 2020)
This paper aimed at examining the impact of information asymmetry on return volatility in both domestic and cross-country stock market perspectives. For this purpose, secondary data were extracted from BSE 100 index as a domestic stock market index; the Ibovespa, the leading stock index of the Brazilian stock market; IMOEX from the Russian stock market; SSE Composite Index of the Chinese stock market; and FTSE/JSE of the South African stock market for the period from January 2007 – December 2017. To assess the impact of information asymmetry on return volatility, the exponential generalized autoregressive conditional heteroskedasticity model (EGARCH) and Glosten, Jagannathan, and Runkle (GJR-GARCH) models were employed. Test results of GARCH family models showed the presence of information asymmetries in return volatility of all five stock market indices. GJR-GARCH model showed that negative shocks caused more volatility in return and EGARCH evidenced that positive shocks caused more volatility in return due to market anomalies that were experienced during the study period.